EFFECIENCY OF SILVER NANOPARTICALES AS ANTIBACTERIAL AGAINST AEROMONAS HYDROPHILA ISOLATED FROM INFECTED COMMON CARP - Suhail, R. N.; Mustafa, S. A.; AL-Obodi , E.E. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present investigation was carried out to investigate the antibacterial efficiency of silver nanoparticles (AgNPs) in vitro against Aeromonas hydrophila using disc diffusion assay and minimum inhibitory concentration. The pathogenic A. hydrophila was isolated from infected common carp, usually diagnosed by chemical methods, and Avitek 2 compact device were used to confirm the diagnosis. The effectiveness of the prepared AgNPs was tested by chemical and biological (green synthesis using lemon extract) methods and were diagnosed by Fourier-transform infrared spectroscopy (FTIR), UV-Visible spectroscopy, Transmission electron microscopy (TEM), scanning electron microscope (SEM), which was spherical shape of the nanosilver and the size ranged between 30-50 nm. Results of disc diffusion assay showed that the chemical synthesized of AgNPs in 18hr recorded the highest inhibition zone followed by the bio-synthesized AgNPs and Oxytetracycline respectively. After 24 hr the highest inhibition zone was registered in Oxytetracycline, however after 5 days bio-synthesized AgNPs showed the higher inhibition zone which was significantly different(P≤0.05) in comparison to other products. Based on these results, both bio and chemical synthesized of AgNPs were effectively act as antibacterial against A.hydrophila. However, green synthesis using lemon extract is considered better antibacterial with low MIC than chemical AgNPs because lemon extract is regarded eco-friendly and also the low cost product compared to chemical AgNPs synthesis.